Role of Spirituality in the Treatment of Work Stress and Mental Health. (An Exploratory Empirical Study of Health Assessment) - Kumar, Sushil (International Journal of Psychosocial Rehabilitation, 2020)
The present study explores the treatment of work stress and mental health.An exploratory empirical study of health assessment of managerial personnel in India.A sample size of 150 employees working in different organization to see the effect of spirituality in the employee workstress and mental health in India health assessment, the scale is used workplace spirituality and general health questionnaire respectively and finding of research that how the spirituality used as a treatment of work-stress and mental health, spirituality have a negative relationship between workstress and mental health. The study also found that workstress harms health while spirituality positively correlated with mental health.The finding also gives the practical benefit of spirituality to reduce the work-stress and employee mental health in the organization. The exploratory study also motivates the future of research to understand how spirituality copes this situation of work-stress and mental health.The Study's significant findings of the study were that most of the mental health professionals based on their orientation and exposure to the same defined spirituality differently. Very few professionals used as part of therapy but encouraged the faith of the clients even if they did not believe in it. When used, spiritual techniques and suggestions were introduced once acute. The symptoms were under control. The use of spirituality was mainly in the case of minor mental illness and the form of supportive therapy. Clients' responses were positive in most cases where spirituality was integrated. Findings further reveal that this integration strengthened rapport and the therapeutic relationship. In cases where the professional's beliefs' about spirituality, especially about treatment contrasted sharply with those of the clients, professionals indicated that they did not let their personal views influence their clients. Most Professionals were of the view that the interest of the client was paramount and not their personal beliefs and views about spirituality. The most common adverse impact reported was that of the client stopping the treatment.